Green babycare - Marriott, Susannah; Moore, Hannah (London Dorling Kindersley, 2008)
Millions of nappies are thrown away every day and much of baby care is far from environmentally friendly; find out how you can make a difference by choosing greener lifestyle choices for you and your family. You can discover how to feed, clothe, clean, entertain and transport your baby in a greener way. You can pick up practical step-by-step advice on using alternatives to chemical products; from how to change a reusable nappy to making a lotion for nappy rash. "Green action boxes" features practical solutions to suit your lifestyle: from recycling toys (light green) to using washable nappies (deeper green). It is suitable for parents who want to make a difference to the environment and protect their baby's future planet
Family corner
Formerly CIP
Includes index
1 13
Keywords: Green products; Infants -- Care; Infants' supplies -- Environmental aspects